Advances in Microfluidic Technologies for Energy and Environmental Applications - Ren, Yong (InTechOpen, 2020)
Microfluidics have aroused a new surge of interest in recent years in environmental and energy areas, and inspired novel applications to tackle the worldwide challenges for sustainable development. This book aims to present readers with a valuable compendium of significant advances in applying the multidisciplinary microfluidic technologies to address energy and environmental problems in a plethora of areas such as environmental monitoring and detection, new nanofluid application in traditional mechanical manufacturing processes, development of novel biosensors, and thermal management. This book will provide a new perspective to the understanding of the ever-growing importance of microfluidics.